Hyponatremia and Congestive Heart Failure: A Marker of Increased Mortality and a Target for Therapy - Adam Romanovsky; Sean Bagshaw; Mitchell H. Rosner (International Journal of Nephrology)
Heart failure is one of the most common chronic medical conditions in the developed world. It is characterized by neurohormonal activation of multiple systems that can lead to clinical deterioration and significant morbidity and mortality. In this regard, hyponatremia is due to inappropriate and continued vasopressin activity despite hypoosmolality and volume overload. Hyponatremia is also due to diuretic use in an attempt to manage volume overload. When hyponatremia occurs, it is a marker of heart failure severity and identifies patients with increased mortality. The recent introduction of specific vasopressin-receptor antagonists offers a targeted pharmacological approach to these pathophysiological derangements. Thus far, clinical trials with vasopressin-receptor antagonists have demonstrated an increase in free-water excretion, improvement in serum sodium, modest improvements in dyspnea but no improvement in mortality. Continued clinical trials with these agents are needed to determine their specific role in the treatment of both chronic and decompensated heart failure.